Seismic behaviour characterization of reinforced concrete buildings - Varum, H. (2012)
The seismic vulnerability assessment associated to existing reinforced concrete buildings, constructed until the late 70’s in many European countries with moderate to high seismic hazard, designed and constructed without considering adequately earthquake provisions, is of extreme importance. They constitute a significant source of risk for our cities. In this paper are presented the main results of research developed in the field of seismic assessment and retrofitting of existing RC buildings.